Agrarian change in Zimbabwe: politics, production and accumulation - Zamchiya, P; Dr. Phillan Zamchiya (2012)
The analysis of agrarian change presented in this thesis integrates state practices and wider politics to the study of rural differentiation, using a case study of Zimbabwe. Most studies of agrarian change in the 21st century have tried to come to grips with rural differentiation in Africa, its causes and effects, by using particular models such as those of neo-classical economics, livelihood approaches, Marxist analysis of accumulation and social and cultural networks, or a combination of variables from the four approaches. However, these theoretical approaches fail to comprehensively integrate the role of the state and politics into the analysis of rural differentiation. My study explains differentiation by exploring beneficiary selection, production and accumulation processes on Zimbabwe’s Fast Track land reform resettlement schemes. Fast Track involved a series of partisan and violent invasions of largely white owned commercial farms from 2000, which constituted the largest land redistribution in post-colonial Africa. Scholars exploring politics and the Zimbabwean state have not applied their insights to an analysis of field based data on production and accumulation on Zimbabwe’s resettlement farms. I argue that the restructuring of the state and politics as an instrument of violence and as a site of accumulation dominated by patronage-both justified through ideology-was central to agrarian change after 2000. I find the three concepts of violence, patronage and ideology more useful in capturing the nuances and modalities of empirical realities on resettlement schemes than neo-patrimonial theories that provide generalised accounts of the African state. Though still acknowledging the role of other differentiating factors such as social networks, hard work by resettled farmers and economic factors, it is through the integration of political processes into the analysis of agrarian change that, I argue, one can understand better the dynamics shaping rural differentiation in post-2000 Zimbabwe.